Fabrication of Metal Alloy-Deposited Flexible MWCNT Buckypaper for Thermoelectric Applications. (8th December 2013) - Liu, Jih-Hsin; Miao, Hsin-Yuan; Lakshmanan, Saravanan; Wang, Li-Chih; Tsai, Ren-Hui
Abstract : We report the fabrication of a flexible network of multiwall carbon nanotubes (MWCNTs) known as buckypaper (BP) for thermoelectric (TE) applications. A thermal evaporation method was used to deposit TE metal alloys onto the BP. The TE properties were improved primarily by increasing the Seebeck coefficient values (50 and 75 μ V/K) and the electrical conductivity by approximately 10 000 S/m. High-temperature resistivity studies were performed to confirm the semiconductivity of buckypaper. Variations in resistivity were observed to be the result of the metal alloys coated on the BP surface. We also demonstrated that a substantial increase in the Seebeck coefficient values can be obtained by connecting 3 and 5 layers of metal-deposited BP in series, thereby enhancing the TE efficiency of MWCNT-based BP for application in thermoelectric devices.